Influence of influent wastewater communities on temporal variation of activated sludge communities. (15th April 2015) - Lee, Sang-Hoon; Kang, Hyun-Jin; Park, Hee-Deung
Abstract: Continuously feeding influent wastewater containing diverse bacterial species to a wastewater treatment activated sludge bioreactor may influence the activated sludge bacterial community temporal dynamics. To explore this possibility, this study tracked influent wastewater and activated sludge bacterial communities by pyrosequencing 16S rRNA genes from four full-scale wastewater treatment plants over a 9-month period. The activated sludge communities showed significantly higher richness and evenness than the influent wastewater communities. Furthermore, the two communities were different in composition and temporal dynamics. These results demonstrate that the impact of the influent wastewater communities on the activated sludge communities was weak. Nevertheless, 4.3–9.3% of the operational taxonomic units (OTUs) detected in the activated sludge were shared with the influent wastewater, implying contribution from influent wastewater communities to some extent. However, the relative OTU abundance of the influent wastewater was not maintained in the activated sludge communities (i.e., weak neutral assembly). In addition, the variability of the communities of the shared OTUs was moderately correlated with abiotic factors imposed to the bioreactors. Taken together, temporal dynamics of activated sludge communities appear to be predominantly explained by species sorting processes in response to influent wastewater communities. Graphical abstract: Highlights: The temporal variation of influent and bioreactor bacterial communities was evaluated. The two communities differed in terms of diversity and composition. Small portion of bioreactor community was shared with influent community. The influent relative species abundance was not maintained in the bioreactor. Species sorting processes explained a majority of the community temporal dynamics.